STATISTICAL EVALUATION OF PERFORMANCE AND TRAINING SATISFACTION AT THE POLICE TRAINING ACADEMY, WUDIL - Musa, Yakubu; Muhammad, Falalu (FUDMA JOURNAL OF SCIENCES, 2025)
This survey research examines the determinants affecting academic achievement and training satisfaction among cadets at the Nigeria Police Academy in Wudil, Kano. The investigation evaluated the relationships between study habits and academic performance (quantified by CGPA), the effect of academic challenges on CGPA, the association between training satisfaction and perceived training relevance, the influence of preferred training methodologies, and the determinants affecting overall satisfaction with academic and training experiences. Statistical analysis indicated a strong positive correlation between study hours and CGPA (r=.311, p<.05) and a considerable negative effect of academic problems on CGPA (r=−.181, p=.028, β=−.221, p=.005). A significant correlation was identified between perceived training relevance and overall satisfaction (χ2, p = .001). A substantial percentage of cadets (34.2%) choose field training, indicating the need of addressing academic challenges and prioritizing practical, experiential training to enhance cadet performance and enjoyment. Study habits markedly improve academic performance, although academic obstacles provide a substantial obstacle. Cadets prioritize pertinent training, especially practical field activities, which is directly associated with increased overall satisfaction. The robust correlation between perceived training relevance and overall pleasure, together with the preference for field training, indicates potential areas for curricular and pedagogical enhancement.